PERSPEKTIF UKM TERHADAP LAPORAN KEUANGAN - Kevin; Kristianti , Ika; Matitaputty, Jean Stevany (Perspektif Akuntansi, 2024)
Small and medium enterprises (SMEs) have an important contribution to the Indonesian economy, as well as to generate jobs. The performance of an entity can be reviewed by their financial statements. Moreover, this financial statement can also be used as the basis of decision making. This research provides the perspective of small and medium enterprises owners from the commercial sector about financial statements. The research method used was qualitative descriptive with resource persons from three successful entrepreneurs in Salatiga. This research finds that financial statements have an important contribution to small and medium enterprises' continuity. Financial statements have a lot of usabilities related to a short-term and long-term plan. Size of company, level of education, and easiness are not the main reason that affects the decision of financial statement-making but have an impact on that. Financial statements made by small and medium enterprises indirectly have applied SAK-EMKM in their making process. The main reason for making a financial statement is because it is used to fulfill the needs of information for decision making.